The positivity bias of Chinese temporal collective self: Evidence from the first-person perspective and the third-person perspective - Yue, Caizhen; Long, Yihong; Ni, Chaomei; Wu, Huating; Zhao, Dexuan (Frontiers in Psychology, 2023)
Objective As a unique part of human thinking, people can project themselves into the past or the future for mental time travel. This study attempts to expand the temporal self into the domain of the collective self. Methods We used an adapted temporal collective self-reference paradigm to probe into the positivity bias of temporal collective self in this study. In Experiment 1, the first-person perspective was adopted for the participants to conduct the temporal collective self-reference processing, and the third-person perspective was adopted for the temporal collective self-reference processing in Experiment 2. Results The findings indicated that no matter from the first-person perspective or the third-person perspective, people show positivity bias in the trait adjectives judgment, response times and recognition rates during the temporal collective self-processing. Discussion This study explores mental time travel on the level of collective self, and contributes to deepening the understanding of temporal collective self.